Sulfate reduction and methanogenesis in the hypersaline deep waters and sediments of a perennially ice‐covered lake. Issue 5 (3rd April 2021) - Saxton, Matthew A.; Samarkin, Vladimir A.; Madigan, Michael T.; Bowles, Marshall W.; Sattley, William Matthew; Schutte, Charles A.; Joye, Samantha B.
Abstract: Documenting anaerobic microbial metabolisms in hypersaline perennially ice‐covered lakes in Antarctica further refines the environmental limits to life and may reveal rare biogeochemical mechanisms and/or novel microbial catalysts of elemental cycling. We assessed rates of sulfate reduction, methanogenesis, and anaerobic oxidation of methane using radiotracers and generated 16S rRNA gene libraries from the microbial communities inhabiting the deep calcium‐chloride‐rich brine and sediments of Lake Vanda, McMurdo Dry Valleys, Antarctica. Sulfate reduction rates were observed in surface sediments but not in the brine overlying the sediments. Methane formation through the methylotrophic, acetoclastic, and hydrogenotrophic pathways was quantified using 14 C‐labeled methylamine, acetate, and CO2, respectively, and methanogenesis was detected in both the brine and the sediments. Hydrogenotrophic methanogenesis rates were the highest of all substrates tested in the sediments, while methylotrophic methanogenesis was highest in the brines. Anaerobic oxidation of methane was below the limit of detection in both the brines and sediments. The major taxa of Bacteria and Archaea detected were most similar to organisms previously observed in hypersaline environments and included examples related to known sulfate‐reducing bacteria other than Deltaproteobacteria (surprisingly, sulfate‐reducing Deltaproteobacteria were not observed in this study), and both methanogenic and methanotrophic Archaea . These data indicate an active microbial community in the anoxic brine of Lake Vanda that while similar in terms of community structure and metabolism to other brine habitats, is uniquely evolved to survive in this extreme environment.